A review of field-based assessments of neuromuscular control and their utility in male youth soccer players - Read, P. J.; Oliver, J. L.; Croix, M. S.; Myer, G. D.; Lloyd, R. S. (The Journal of Strength and Conditioning Research, 2019)
Lower-extremity injuries in male youth soccer are common and equate to a substantial time loss from training and competitions during the course of a season. Extended periods of absence will impact player involvement in skill and physical development activities, as well as participation in competitive match play. Neuromuscular risk factors for lower-extremity injury in male youth soccer players can be categorized into quadriceps dominance, leg dominance, ligament dominance, trunk dominance, and reduced dynamic stability. Valid screening methods to identify risk factors that are practically viable are needed for youth athletes who may be at a greater risk of injury in soccer. Although field-based tests of neuromuscular control provide a reliable option for the assessment of injury risk in adults and females, less data are available in male youth soccer players, and further research is required to examine their ability to predict injury risk. This article provides a review of the current literature pertaining to field-based screening tests and critically appraises their suitability for use with male youth soccer players. Currently, the only method that has been validated in male youth soccer players is the landing error scoring system. Asymmetrical anterior reach measured during the Y-Balance test may also be considered because of its strong predictive ability in male youth basketball players; however, further research is required to fully support its use with soccer players.